Salt Packaging Redesign Using Quality Function Deployment (Qfd) Method to Increase Sales (Case Study: Saboh Hate Farmers Group, Kuala Idi Cut, East Aceh): Redesain Kemasan Garam Menggunakan Metode Quality Function Deployment (Qfd) untuk Meningkatkan Penjualan (Studi Kasus: Kelompok Tani Saboh Hate, Kuala Idi Cut, Aceh Timur) - Saputra, Dian; Handayani, Nurlaila; Yusnawati (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2023)
Salt is one of the great potentials on the coast of East Aceh Regency which can be developed to boost the economic growth of the community. The location of the research was carried out in the Saboh Hate group located in Darul Aman District, Kuala Idi Cut Village, Aron Muda Hamlet, East Aceh Regency, Aceh Province. Currently, the salt on the market has an attractive packaging design, while the Saboh Hate Farmers Group does not yet have a good or simple packaging, so research is needed to design packaging that can increase competitiveness. The purpose of this study is to determine the characteristics of the salt packaging that consumers want at the Saboh Hate Farmer Group through packaging redesign. The method used is statistical test and Quality Function Deployment (QFD). The research phase includes observation and interviews through questionnaires and processing data through statistical tests, SPSS 20 and House of Quality (HOQ). The results show the characteristics of the salt packaging that consumers want based on the relative weight results including the information needed for salt packaging including weight, halal brand and logo with a value of 28.28%, the salt packaging material used is ordinary clear plastic with a value of 24.27%, The color of the desired salt packaging design is blue with a value of 23.71 and the size of the salt packaging that consumers want is generally a 250 g package with a value of 23.71%.